The Burden of the Serious and Difficult-to-Treat Infections and a New Antibiotic Available: Cefiderocol - Taheri, Yasaman; Joković, Nataša; Vitorović, Jelena; Grundmann, Oliver; Maroyi, Alfred; Calina, Daniela (Frontiers in Pharmacology, 2021)
Background Infection is a disease that can occur due to the entrance of a virus, bacteria, and other infectious agents. Cefiderocol is innovative cephalosporin drug that belongs to a special class of antibiotics, sideromycins, which are taken up by bacterial cells through active transport. The unique cell entry and stability to β-lactamases allow cefiderocol to overcome the most common resistance mechanisms in Gram-negative bacteria. Objective This article aims to highlight the therapeutic efficacy, safety and tolerability of Cefiderocol, with a focus on the FDA label. Methods The pharmacological properties of Cefiderocol are also summarized. In this review, we conducted literature research on the PubMed database using the following keywords: “antimicrobial treatment”, “new antibiotic”, “Cefiderocol”, “siderophore cephalosporin”; “multidrug-resistant”, “Gram-negative bacilli”, “critically ill patients”; “severe bacterial infections”. Results There were identified the most relevant data about the pathophysiology of serious bacterial infections, antibacterial mechanism of action, microbiology, mechanisms of resistance, pharmacokinetic and pharmacodynamic properties of Cefiderocol. Conclusion The results highlighted there appeared to be clinical benefit from cefiderocol in the treatment of infections caused by Gram-negative aerobic microorganisms in adult patients with severe infections and limited treatment options.